PENGARUH KUALITAS PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP TINGKAT PENGEMBALIAN DAN RISIKO PEMBIAYAAN BANK SYARIAH DI INDONESIA - Budiman, Fathan (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2016)
The emergence of concept of Good Corporate Governance (GCG) is basedon agency theory that expects the disclosure of information so that conflictsof interest among the principal agent can be minimized. Conflicts of interestcan occur in any company including Islamic banking. This situation is recognized by Bank Indonesia, which then requires the application of the principles of GCG in Bank Indonesia regulations at PBI No. 8/4 / PBI / 2006. The purpose of this study was to describe the quality of the implementation of Good Corporate Governance of Islamic Banking in Indonesia and to analyze their effects on the financial performance and operational efficiency. Financial performance is measured by earnings (ROA), and liquidity (FDR). The object of this study is Islamic banking companies that issue an annual report and a report on the implementation of Good Corporate Governance period of 2013-2015 in accordance with Circular Letter No. BI. 12/13/BPbs on April 30, 2010. Types of data used are secondary data from a composite ranking score of Good Corporate Governance as measured by 11 indicators for BUS and 5 indicators for UUS, and ratio ROA, and NPF. The variables were analyzed using simple linear regression analysis. The results showed that the quality of the implementation of Good Corporate Governance (GCG) has negative effect on the return of Islamic banks measured by profitability (ROA) and a significant negative effect on the risk financing Islamic bank as measured by asset quality (NPF).